Out-of-Hospital Fluid in Severe Sepsis: Effect on Early Resuscitation in the Emergency Department - Seymour, Christopher W. (2010)
BACKGROUND: Early identification and treatment of patients with severe sepsis improves outcome, yet the role of out-of-hospital intravenous (IV) fluid is unknown. OBJECTIVE: To determine if the delivery of out-of-hospital fluid in patients with severe sepsis is associated with reduced time to achievement of goal-oriented resuscitation in the emergency department (ED). METHODS: We performed a secondary data analysis of a retrospective cohort study in a metropolitan, tertiary care, university-based medical center supported by a two-tiered system of out-of-hospital emergency medical services (EMS) providers. We studied the association between delivery of out-of-hospital fluid by advanced life support (ALS) providers and the achievement of resuscitation endpoints (central venous pressure [CVP] ≥8 mmHg, mean arterial pressure [MAP] ≥65 mmHg, and central venous oxygen saturation [ScvO(2)] ≥70%) within six hours after triage during early goal-directed therapy (EGDT) in the ED. RESULTS: Twenty five (48%) of 52 patients transported by ALS with severe sepsis received out-of-hospital fluid. Data for age, gender, source of sepsis, and presence of comorbidities were similar between patients who did and did not receive out-of-hospital fluid. Patients receiving out-of-hospital fluid had lower out-of-hospital mean (± standard deviation) systolic blood pressure (95 ± 40 mmHg vs. 117 ± 29 mmHg; p = 0.03) and higher median (interquartile range) Sequential Organ Failure Assessment (SOFA) scores in the ED (7 [5–8] vs. 4 [4–6]; p = 0.01) than patients not receiving out-of-hospital fluid. Despite greater severity of illness, patients receiving out-of-hospital fluid approached but did not attain a statistically significant increase in the likelihood of achieving MAP ≥65 mmHg within six hours after ED triage (70% vs. 44%, p = 0.09). On average, patients receiving out-of-hospital fluid received twice the fluid volume within one hour after ED triage (1.1 L [1.0–2.0 L] vs. 0.6 L [0.3–1.0 L]; p 0.01). No difference in achievement of goal CVP (72% vs. 60%; p = 0.6) or goal ScvO(2) (54% vs. 36%; p = 0.25) was observed between groups. CONCLUSIONS: Less than half of patients with severe sepsis transported by ALS received out-of-hospital fluid. Patients receiving out-of-hospital IV access and fluids approached but did not attain a statistically significant increase in the likelihood of achieving goal MAP during EGDT. These preliminary findings require additional investigation to evaluate the optimal role of out-of-hospital resuscitation in treating patients with severe sepsis.